Palmoplantar keratoderma caused by a missense variant in CTSB encoding cathepsin B. (1st January 2021) - Mohamad, J.; Samuelov, L.; Malki, L.; Peled, A.; Pavlovsky, M.; Malovitski, K.; Taiber, S.; Adir, N.; Rabinowitz, T.; Shomron, N.; Milner, J. D.; Lestringant, G.; et al.
Summary: Background: Palmoplantar keratoderma (PPK) refers to a large group of disorders characterized by extensive genetic and phenotypic heterogeneity. PPK diagnosis therefore increasingly relies upon genetic analysis. Aim: To delineate the genetic defect underlying a case of diffuse erythematous PPK associated with peeling of the skin. Methods: Whole exome and direct sequencing, real‐time quantitative PCR, protein modelling and a cathepsin B enzymatic assay were used. Results: The patient studied had severe diffuse erythematous PPK transgrediens. Pedigree analysis suggested an autosomal dominant mode of inheritance. Whole exome sequencing revealed a heterozygous missense mutation in the CTSB gene, encoding the cysteine protease cathepsin B. Genomic duplications in a noncoding region, which regulates the expression of CTSB, were recently found to cause erythrokeratolysis hiemalis, a rare autosomal dominant disorder of cornification. This mutation affects a highly conserved residue, and is predicted to be pathogenic. Protein modelling indicated that the mutation is likely to lead to increased endopeptidase cathepsin B activity. Accordingly, the CTSB variant was found to result in increased cathepsin B proteolytic activity. Conclusion: In summary, we report the identification of the first gain‐of‐function missense mutation in CTSB, which was found to be associated in one individual with a dominant form of diffuse PPK.